Fermentation of poultry manure for improving its quality and safety as ruminant feed - Sharmeen Islam; A. K. M. Ahsan Kabir; Md. Rokibul Islam Khan (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Poultry manure (PM) is a concern for Bangladesh. The improvement of quality and safety is always desirable. The experiment assesses the quality and safety parameters of PM with the addition of Saccharomyces cerevisiae and indigenous microorganisms (IMO) in different fermentation conditions (aerobic, facultative anaerobic, and anaerobic) for 7 days.